Effect of bone loss on the fracture resistance of narrow dental implants after implantoplasty. An in vitro study - Leitão-Almeida, Bruno (2021)
Background: Implantoplasty (IP) involves polishing of the exposed surface of implants affected by peri-implantitis (PI). A study was made to determine whether the degree of bone loss influences the fracture resistance of implants with or without IP. Material and Methods: An in vitro study was carried out on 32 narrow (3.5 mm) dental implants with a rough surface and external hexagonal connection. Implantoplasty was performed in half of the implants of the sample. Both the IP and control implants were divided into two subgroups according to the amount of bone loss (3 mm or 7.5 mm). Standardized radiographic assessment of implant width was performed using specific software. The main outcome variable was the maximum compression force (F-max) of implants when subjected to static resistance to fracture tests. Implant fractures were subsequently analyzed by scanning electron microscopy. A descriptive and bivariate analysis of the data was performed. Results: Significant changes in implant width were observed after IP (p<0.05). No significant differences between IP and control implants were recorded in terms of the F-max values in the two bone loss subgroups (3 mm: control 854.37N +/- 195.08 vs. IP 752.12N +/- 186.13;p =0.302, and 7.5 mm: control 548.82N +/- 80.02 vs. IP 593.69N +/- 111.07; p-0.370). Greater bone loss was associated to a decrease in F-max which proved significant for the control implants (p=0.001). Fractures were more frequently located in the platform (n=13). Conclusions: Implants with more apical bone levels appear to be more susceptible to fracture. On the other hand, IP does not seem to significantly decrease the fracture resistance of narrow (3.5 mm) platform dental implants with external hexagonal connections. The fact that most fractures occur in the platform area indicates that the latter is exposed to more mechanical stress.